The strange case of a hematocele mistaken for a neoplastic scrotal mass - barale, maurizio; Oderda, Marco; Faletti, Riccardo; Falcone, Marco; Pisano, Francesca; Marra, Giancarlo; Cassenti, Adele; Delsedime, Luisa; Pacchioni, DOnatella; Gontero, Paolo (Canadian Urological Association Journal, 2015)
Hematoceles are usually associated with a history of scrotal trauma, are usually painful and rarely have an idiopathic origin. We describe the peculiar case of a hematocele mistaken for a testicular cancer.